2020
DOI: 10.15766/mep_2374-8265.10878
|View full text |Cite
|
Sign up to set email alerts
|

Improving Learners' Comfort With Cesarean Sections Through the Use of High-Fidelity, Low-Cost Simulation

Abstract: Introduction: Several studies have demonstrated effective simulation-based training for laparoscopic procedures in OB/GYN, but limited simulation curricula exist for abdominal procedures, particularly cesarean sections (CSs). Methods: We developed a high-fidelity modification of an existing CS model costing about $25 and incorporated it into a 90-minute teaching simulation event for medical students and OB/GYN residents in a single academic program. The simulation included a structured curriculum, pre-/postsim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous literature reviews mentioned that this mannequin became an excellent simulation media [ 28 ]. Furthermore, a recent study claimed cesarean section practice using mannequin simulation demonstrated important knowledge improvement, particularly in suturing ability [ 29 ]. Simulation of clinical practice improved performance more than a single video tutorial in medical students [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature reviews mentioned that this mannequin became an excellent simulation media [ 28 ]. Furthermore, a recent study claimed cesarean section practice using mannequin simulation demonstrated important knowledge improvement, particularly in suturing ability [ 29 ]. Simulation of clinical practice improved performance more than a single video tutorial in medical students [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation of clinical practice improved performance more than a single video tutorial in medical students [ 19 ]. This method allowed residents to gain experiment chances repeatedly along with a minimum stress environment [ 29 ]. Simulation using a mannequin is considered as a complementary medium for learning caesarean section, because the mannequin can be adjusted similar to the management of patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it allows everyone to learn at their own pace, without fear and stress of having viral transmission. The efficacy of simulation training has been replicated in many areas in medical and surgical practice [7,8]. It also encourages realistic team-based communication training and allows the retention of knowledge and skills for a longer duration [9].…”
Section: Discussionmentioning
confidence: 99%